The Image of Islam in Ms Marvel Series: An Analysis of Reception among Indonesian Muslim Audiences - Saputra, Muhammad Irawan; Dewanto Putra fajar (Jurnal Komunikasi Islam, 2023)
The issue of Islamophobia has become a major concern of discussions, including regarding the representation of Muslims in Hollywood films, where Muslim characters are often portrayed as terrorists or perpetrators of violence. However, recently several Hollywood films are trying to create positive representations of Islam and Muslims, for example Ms Marvel film series, which features a Muslim superhero. This study aims to examine how Muslim audiences in Indonesia interpret the depiction of Islam in the Ms Marvel film series. The reception analysis is used to observe phenomena related to audience interpretation. The findings have illustrated that the Muslim audience tends to take exact acceptance of Hollywood’s depiction of how Muslims dress in this film, which is called a dominant hegemonic position. However, some respondents have the opposite acceptance position and the negotiated position as well.